Impact of home-based follow-up care intervention on health-related quality of life among hypertensive patients at a teaching hospital in Ilorin, Nigeria - Akeem, Bolarinwa Oladimeji (2016)
Introduction: The usual care for hypertension within hospital settings in Nigeria is characterized by poor medical outcomes and poor health related quality of life (HRQoL). Of those few studies that have implement home based interventions on hypertension, not many of them used HRQoL as an outcome measure. This study developed, implemented and assessed the impact of home based follow-up care on HRQoL of hypertensive patients attending outpatients’ clinics in Ilorin, Nigeria. Methodology: An individual open (un-blinded) Randomized Controlled Trial (RCT) was conducted among 229 consented hypertensive patients in two outpatients’ clinics of University of Ilorin Teaching Hospital, Ilorin, Nigeria using systematic random sampling. A total of 149 and 150 patients were randomly allocated to intervention and control groups respectively. The intervention was a six month taskshifting (Nurse driven) home based follow-up care. The primary outcome measurement was HRQoL. Data was collected with the use of pretested questionnaire that contained validated SF36v2 and MMAS-8 tools for the assessment of HRQoL and medication adherence respectively. Data was analyzed with intention-to-treat principle. The SPSS version 22 software was used for analysis and both descriptive and inferential statistics were presented. Treatment effects were measured with the t-tests, ANCOVA and MANCOVA analysis. Significant levels were set at p-value of <0.05 and 95% Confidence Interval (CI). Results: A total of 29 and 31 patients dropped out of intervention and control groups respectively, making a combined attrition rate of 20.1% in this study. At baseline only general health (50.44) and vitality (52.68) of the 8 subscales of HRQoL had better score than the reference population average of 50.00 (+10). Both physical and mental components of the HRQoL were below population average. The between group treatment effect was not statistically significant (p>0.05) while within group treatments effects were statistically significant for both intervention and control arms (p<0.05). After controlling for age and baseline HRQoL, intervention group had improved physical component of HRQoL than the control group. The intervention group also had statistically significant improvement in blood pressure control, medication adherence and symptom counts (p<0.05). Conclusion: The home based follow-up care intervention by this study was shown to impact positively on physical component of HRQoL after controlling for baseline HRQoL and age of the patients. Symptom count, medication adherence and blood pressure control were positively impacted upon by the home based follow-up intervention.